Human Capital Transformation: Building a Resilient and Agile Workforce - Riska Fii Ahsani; Hanung Eka Atmaja; Nur Wulan Intan Palupi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of Human Capital Transformation on organizational agility and its subsequent effects on workforce resilience and agility. Employing a quantitative approach with random sampling, data was collected from 397 employees at PT Panasonic Manufacturing Indonesia through an online questionnaire. The research utilized Smart PLS for analysis to examine both direct and indirect effects among the variables. The results reveal that Human Capital Transformation significantly enhances organizational agility, which in turn positively influences workforce resilience and agility. Specifically, organizational agility mediates the relationships between Human Capital Transformation and both workforce resilience and agility. The findings underscore the importance of integrating human capital development with agile organizational practices to improve workforce adaptability and performance. This research provides insights into how organizations can effectively leverage human capital strategies to foster a more resilient and agile workforce, thereby maintaining a competitive edge in a dynamic business environment.